The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/acs.orglett.9b02171
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Cyclometalated Oxazoline Gold(III) Complex-Catalyzed Asymmetric Carboalkoxylation of Alkynes

Abstract: Asymmetric catalysis by using novel chiral O,O′-chelated 4,4′-biphenol cyclometalated oxazoline gold­(III) complexes has been developed. A high yield (≤89%) and a high enantioselectivity (≤90% ee) were achieved in asymmetric carboalkoxylation of alkynes. Enantioselectivity could be significantly improved from 19% to 90% ee by increasing the steric size of the substituent on the chiral oxazoline ligand. Catalytically active AuIII species and the origin of chiral induction are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 60 publications
(17 reference statements)
0
30
0
Order By: Relevance
“…Although the enantioselectivity level was far from practical (Scheme 35), especially in comparison to the bisphosphine ligand used in the seminal work of Toste [122], the high yield proved excellent catalytic activity. Recently, Wong proved that formation of indanone 183 could catalyzed by the cyclometalated gold(III) complexes 184 [123].…”
Section: Furan Pyrrolidine and Indanone Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the enantioselectivity level was far from practical (Scheme 35), especially in comparison to the bisphosphine ligand used in the seminal work of Toste [122], the high yield proved excellent catalytic activity. Recently, Wong proved that formation of indanone 183 could catalyzed by the cyclometalated gold(III) complexes 184 [123].…”
Section: Furan Pyrrolidine and Indanone Derivativesmentioning
confidence: 99%
“…Catalysts 2019, 9, x FOR PEER REVIEW 26 of 40 catalytic activity. Recently, Wong proved that formation of indanone 183 could catalyzed by the cyclometalated gold(III) complexes 184[123]. The synthesis of indanone via carboalkoxylation.…”
mentioning
confidence: 99%
“…The study of Au(III) chemistry is much more challenging both experimentally and theoretically, because these complexes are usually very reactive and difficult to synthesize. However, in recent years, many studies on the catalytic efficiency of Au(III) have been carried out, motivated by the expected more efficient activation of double and triple C-C bonds due to the larger Lewis acidity of the metal in its +3 oxidation state [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. First studies were devoted to synthesize stable Au(III) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Wong's group reported another work of asymmetric gold(III) catalysis by using chiral O,O‐chelated biphenol/C,N‐cyclometallated oxazoline gold(III) complexes (Scheme 41). [57] When biphenol was employed as the ligand in replace of BINOL, the O,O‐chelation mode was adopted without tautomerization. By screening of a series of (O,O)/(C,N)‐gold(III) catalysts and (C,O)/(C,N)‐gold(III) complexes, the authors found the chirality of BINOL or biphenol ligands contribute little to the reaction enantioselectivity, while the enantioselectivity is mainly related to the chiral substituent group on the oxazoline ligand.…”
Section: Recent Development Of Enantioselective Gold(iii) Catalysismentioning
confidence: 99%